Wrapped Lomax Distribution :a New CircularProbability Model - Subba Rao, R; Ravindranath, V; V.Dattatreya Rao, A; Prasad, G; Ravi Kishore, P (International Journal of Engineering and Technology, 2018)
Lomax Distribution (Pareto Type IV) is fitted for a life time random variable which can be studied for the data belongs to Actuarialscience, medical diagnosis and Queuing theory etc. In the time of day events observed in cycles like hourly, daily, weekly, monthlyor yearly are in circular distribution. By adopting the technique of wrapping an attempt is made to identify a new circular probabilitymodel originate as Wrapped Lomax Distribution. The concept of circular model is introduced and strategy of wrapping is given forLomaxDistribution. Wrapped Lomax Distribution PDF and CDF are derived, their graphs are also studied. The trigonometric momentsand characteristic function of Wrapped Lomax Distribution are obtained and their graphs are also depicted. The characteristics likemean, variance, skewness, kurtosis and circular standard deviation for various values of location and scale parameters are derived in this paper.
Keywords: characteristics; circular probability model; trigonometric moments; wrapped Lomax distribution; wrapping .